Environmental study about Sirte Sabkhas impact on the surface salinity at western coastal of Libya using MODIS satellite techniques. (Journal of Humanitarian and Applied Sciences, 2023)
In this study, MODIS sensor techniques were used because of its quality  images, and its data is available for seven years (2015-2021) to surface salinity in the study area. It was discovered that Sirte sabkhas contribute in the surface salinity of the Libyan western coast. Surface salinity degrees were more intense into summer and spring seasons and less in winter and autumn seasons due to feeding of Sirte sabkhas. The south, southeast and southwest winds had an important role in Sirte sabkhas effect on  surface salinity in the western coast. The differences between salinity values ​​during  study seasons  considered evidence on the sabkhas impact.
Keywords: Libya; Surface; salinity; Sabkhas; MODIS; Sirte